Studi Komparasi Api dalam Teks dan Kontek Ritual; Agnihotra, dan Catur Brata Penyepian - I Nyoman Raka (Tampung Penyang, 2021)
Fire is the process of oxidizing heat, oxygen, and combustible materials. Besides producing fire, the oxidation process of these elements also produces heat and light. Related to this, Hindus in Bali recognize three types of fire or Agni, namely: Ahavaniya Agni, which is a sacred fire for cooking food, Grhapatya Agni is a fire for marriage ceremonies to maintain the sanctity of marriage, Cita Agni is a sacred fire for burning corpses. Many scripture texts discuss fire, which can be used as a reference in the practice of religious life for the Hindu community in Bali, both in reg, sama, atarwa veda, etc. In Wedaparikrama: 44-45 it is explained that fire is an introduction to the ceremony that connects humans with Sang Hyang Widhi Wasa. At the symbolic level, fire has many meanings, including: fire means spirit, fire means purification, fire also means enlightenment. In the practice of chess brata loneliness, fire is used symbolically, both outside and inside for purification purposes. This paper reveals the use of inner fire, namely the fire of self-purification, in the practice of celebrating Nyepi in Balinese tradition. Literature study on fire, found many texts, which can be used as a reference for life practices, especially in ceremonial practices for the Balinese people. The results of interviews, and observations, on the practice of celebrating the holy day of Nyepi through the implementation of chess brata sepian found that the practice of chess brata sepian is a process of self-purification through fire to increase self-purity.